The Model Development of Internal Factors Promotion to Protect Drug Substances Abuse of Female Adolescents - นายาว, สุภาวดี; ศิริโสภณ, ณัฐกฤตา; บุญช่วยธนาสิทธิ์, กรัณฑรัตน์ (Journal of The Royal Thai Army Nurses, 2019)
The objective of the research was to developed the model for internal factors promotion to protect drug substances abuse of female adolescents. The step to create the model were review literature, pilot study about how to adolescents exposed to illicit drugs in Thailand, field study by In-depth interview expertise in branch illicit drugs prevention and treatment, parents and teachers. Moreover did focus group in high risk female adolescents after that analyzed data to do draft model. Evaluated standard of the model by 10 expertise. The name of the model was “POInT In Trust Me Model” Components of the model were Principle of the model = P, Objective of the model = O, Instructor = In, Target group = T, Information /Content of the model = In,Trust activity = Trust and Model evaluation = Me Standard of the model was very good (mean = 3.9, Total 5 scores) and performance manual was very good (mean = 3.71, Total 5 scores)